Who Received Informal Social Support During the First COVID-19 Lockdown in Germany, and Who Did Not? The Role of Social Networks, Life Course and Pandemic-Specific Risks - Ariane Bertogg; Sebastian Koos (Social Indicators Research, 2022)
In this article, we study the receipt of informal support during the first wave of the COVID-19 pandemic in Germany. The containment measures have had various, far-reaching consequences for the wellbeing of people, creating demands for economic, practical, and emotional support—even among individuals who hitherto were not in need of support. Existing research has shown substantial levels of informal support during the pandemic, often based on individuals' existing social networks, but has predominantly taken the perspective of donors. In this article, we focus on the "demand" or recipient "side" of informal support, and ask: (1) Who receives which type of informal social support during the pandemic? (2) Who reports unmet need? (3) Which factors explain support receipt, unmet need and the type of support received? To explain patterns of receiving social support, we identify "classic" life course and "new" pandemic-specific risks and complement this perspective with individuals' support potentials from their social networks. Empirically, we use data from an online survey, collected among a quota sample of the German population (n0.167em=0.167em4,496) at the end of the first lockdown in late spring 2020. Our analysis shows that one in six respondents received social support, while only 3% report unmet need. Practical and emotional support are most widespread. Using logistic and multinomial logistic regression models our results show that social support in general and the type of support received can be explained by life course and pandemic risks, while unmet need is mainly a consequence of social network structure.
Keywords: 300; Social support; Informal Help; Need; Receiving; Solidarity; COVID-19 pandemic; Life Course; Social Networks